Vision correction from digital screens - Jiang, Yan (Nanyang Technological University, 2023)
Lots of people are wearing glasses or contact lenses to correct their vision problems such as short-sightedness, far-sightedness, etc. We engineer a super- high resolution of the digital to be a light field display which generates the correct light field to the eyes and renders sharp images on the retina without having the user wear spectacles. In this dissertation, we built the geometrical relationship between display and retina, then solve the optimization problem by using L-BFGS when modifying the content on a display. Algorithms are all realized by Python and also we show the feasibility of this thought at last.